Use of (S)-(+)-1-aminoindan, (S)-(+)-1-indanol and (1R, 2S)-(+)-cis-1-amino-2-indanol as chiral modifiers in the enantioselective hydrogenation of ethyl pyruvate with Pt/SiO2 catalysts - Merlo, Andrea Beatriz (2008)
In this work it is studied the enantioselective hydrogenation of ethyl pyruvate using a Pt/SiO2 catalyst, modified with different chiral auxiliaries: (S)-(+)-1-aminoindan, (1R, 2S)-(+)-cis-1-amino-2-indanol and (S)-(+)-1-indanol. Cinchonidine modified system was taken as reference. It is analyzed the influence of the particle size of the catalyst, the molecular structure of the modifier and the nature of the solvent. The enantioselective hydrogenation of ethyl pyruvate resulted to be a structure-sensitive reaction, and accordingly, the Pt/SiO2 (B) catalyst (dp = 6.5 nm) provided the best results. The modifier (S)-(+)-1-aminoindan presented an ee of 63%, whereas (S)-(+)-1-indanol gave a racemic mixture and (1R, 2S)-(+)-cis-1-amino-2-indanol showed an effect of "erosion of enantiomeric excess". Concerning the solvent, a higher ee in 2-propanol was obtained when the modifier used was the (S)-(+)-1-aminoindan, while in toluene, n-heptane and acetic acid the performance of the catalytic systems was not good.